2008
DOI: 10.1097/hjh.0b013e3282fbcedf
|View full text |Cite
|
Sign up to set email alerts
|

Masked hypertension: a systematic review

Abstract: The purpose of this research was to review the literature on masked hypertension. Studies, reviews and editorials on masked hypertension were identified by PubMed, Pascal BioMed and Cochrane literature systematic searches. Then, we carried out a meta-analysis of the six cohort studies reporting quantitative data for masked hypertension prognosis. There is still no clear consensus definition of masked hypertension and the reproducibility of the phenomenon is unknown. Nevertheless, the prevalence of masked hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
1
18

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(148 citation statements)
references
References 57 publications
(137 reference statements)
7
122
1
18
Order By: Relevance
“…Ambulatory BP level had already many years ago been shown to be better predictor for cardiovascular complications as compared to clinic BP readings [24,25]. This was confirmed by prospective studies dealt with estimation of outcomes in patients with different BP phenotypesrisk of myocardial infarction, stroke, lethal outcomes and other cardiovascular complications was significantly higher in masked uncontrolled hypertension as compared to normotension and well controlled hypertension and was similar to cardiovascular risk in sustained hypertension [7,[26][27][28][29]. For instance, in accordance to Satoh M. et al data [29] (with mean follow-up of 17.1 years) the risk of stroke in masked un-АГТ -38,8% зимой и 27,8% летом.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Ambulatory BP level had already many years ago been shown to be better predictor for cardiovascular complications as compared to clinic BP readings [24,25]. This was confirmed by prospective studies dealt with estimation of outcomes in patients with different BP phenotypesrisk of myocardial infarction, stroke, lethal outcomes and other cardiovascular complications was significantly higher in masked uncontrolled hypertension as compared to normotension and well controlled hypertension and was similar to cardiovascular risk in sustained hypertension [7,[26][27][28][29]. For instance, in accordance to Satoh M. et al data [29] (with mean follow-up of 17.1 years) the risk of stroke in masked un-АГТ -38,8% зимой и 27,8% летом.…”
Section: Discussionsupporting
confidence: 57%
“…Уже мно-го лет назад был доказан факт, что амбулаторное АД -луч-ший предиктор сердечно-сосудистых осложнений по сравнению с показателями клинических измерений [24,25]. Это подтверждают и проспективные исследования, по-священные оценке исходов при разных фенотипах АД, -риск инфаркта миокарда, мозгового инсульта, летальных исходов и других сердечно-сосудистых осложнений при скрытой АГ значимо выше, чем при нормотонии и эф-фективной АГТ, а также сопоставим с риском при устойчивой АГ [7,[26][27][28][29]. Например, в исследовании Satoh M. и соавт.…”
Section: Discussionunclassified
“…In a systematic review of MH published recently, Bobrie et al [20] concluded that compared with subjects with normal BP or WCH, patients with MH "clearly have a higher BMI, and may even be obese". This conclusion is based in part on a report concerning 3400 treated hypertensive patients in Japan, in whom BMI ≥ 25 was an independent predictor of MH according to home BP monitoring (adjusted OR 1.38), whereas low BMI was predictive of WCH (adjusted OR 0.70) [21].…”
Section: White-coat and Masked Hypertensionmentioning
confidence: 97%
“…They also provide better precision by capturing the BP fluctuations related to daily life and make it possible to capture "masked" hypertension, defined as elevated daytime ambulatory BP (≥135/85 mmHg) in the face of normal office BP (<140/90 mm Hg). The prevalence of masked hypertension has been estimated to be between 8-30% in the general population (201)(202)(203)(204). Several population-based studies and prospective clinical trials have provided clear evidence of the superiority of ambulatory over office BP measures in predicting cardiovascular risks (152,(205)(206)(207)(208).…”
Section: Methodological Characteristicsmentioning
confidence: 99%